Project modifications and bidding in highway procurement auctions - Dakshina G. De Silva; Timothy Dunne; Georgia Kosmopoulou; Carlos Lamarche (Federal Reserve Bank of Atlanta, 2015)
This paper examines bidding behavior in a setting where post-bid-letting project modifications occur. These modifications change both the costs and payouts to the winning contractor, making the contract incomplete. Recent empirical research shows that bidders incorporate the likelihood of such changes in contracts into their bidding strategies. In particular, contractors may adjust bids to compensate for renegotiation, resequencing of tasks, and other costs associated with project modifications. This paper extends this literature by examining bidding behavior and project modifications in Texas, where there has been a significant shift in change order policy. Specifically, Texas sharply reduced its spending on change orders starting in the mid-2000s. In the period before the change in policy, we estimate that project modifications raised bidder costs by 4 percent to 6 percent. In the period after the change in policy, the impact of project modifications on bidder costs is estimated to be closer to 1 percent.
Keywords: D4; L1; L2; 330; procurement auctions; incomplete contracts